2014
DOI: 10.1111/hsc.12113
|View full text |Cite
|
Sign up to set email alerts
|

LGBT people's knowledge of and preparedness to discuss end-of-life care planning options

Abstract: Despite the devastating impact of HIV/AIDS, end-of-life care planning among lesbian, gay, bisexual and transgender (LGBT) communities is relatively under-researched, especially in Australia. This paper reports findings of a survey of 305 LGBT people living in New South Wales, which examined their knowledge of and attitudes towards end-of-life care. The focus of this paper is their preparedness to discuss with healthcare providers any end-of-life care plans. The results highlight that while the majority of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 18 publications
0
49
0
5
Order By: Relevance
“…First, the findings of two studies displayed in the top of the table converged to strongly suggest that very few LGBT people, perhaps only one in every ten, engage in EOL discussions with their primary health care providers (10% to 13%). Moreover, among those who did discuss EOL preferences with their providers, nearly all (92%) raised the issue themselves (Hughes & Cartwright, 2014). Moving down the table, there appears to be evidence of protective factors related to being a member of the LGBT community.…”
Section: Prevalence Of Eol Preparationsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the findings of two studies displayed in the top of the table converged to strongly suggest that very few LGBT people, perhaps only one in every ten, engage in EOL discussions with their primary health care providers (10% to 13%). Moreover, among those who did discuss EOL preferences with their providers, nearly all (92%) raised the issue themselves (Hughes & Cartwright, 2014). Moving down the table, there appears to be evidence of protective factors related to being a member of the LGBT community.…”
Section: Prevalence Of Eol Preparationsmentioning
confidence: 99%
“…Also, more than 90% of the aggregate sample was non-Hispanic white people, approximately one-half of whom were partnered or married. Five of the studies were reported in peer-reviewed journals (Hughes & Cartwright, 2014;Hughes & Cartwright, 2015;Witten, 2014;Witten, 2015;Witten, 2016) while two others were nonpeer-reviewed publications (Fredriksen-Goldsen et al, 2011;MetLife Mature Market Institute, 2010) and one was presented as a webinar (de Vries et al, 2016).…”
Section: Sample Descriptionmentioning
confidence: 99%
See 3 more Smart Citations